RESOURCES TO FACILITATE AND IMPROVE LEARNING PERFORMANCE - Wahyu Setyadi; M Khabib Sulistiyo; Ramaini Ramaini; Idarwanto Idarwanto; Atthoharoh Atthoharoh; Muhammad Nuzli (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2023)
This study aims to describe: what are the appropriate resources in PAI learning, and how the role of teachers as resources in PAI learning at SMA Negeri 13 Merangin. Qualitative research method, data collection techniques of observation, interview, and documentation, and analyzing the data that has been obtained using data analysis, namely data reduction, data presentation, and data verification. The results obtained from this study are that the 11th grade PAI learning of SMA Negeri 13 Merangin uses resources in accordance with the material to be studied, as well as using supporting tools such as props and infokus to explain learning materials, and the PAI teacher of SMA Negeri 13 Merangin is also someone who is professional in his field. The conclusion obtained from the results of this study is that the educational technology resources in SMA Negeri 13 Merangin are good both in terms of resources of tools, materials, devices, people, and the learning environment has gone well.